USING INDEX FOR ASSESSMENT OF WATER QUALITY AND CLASSIFICATION OF EUTROPHICATION LEVELS IN THE QUANG NINH - HAI PHONG COASTAL AREA - Nam, Le Van; Nghi, Duong Thanh; Ngan, Le Thi Kim (Vietnam Journal of Marine Science and Technology, 2018)
With the fast economic growth and the loose management of pollutants discharged into the sea, the Quang Ninh - Hai Phong coastal water faces the risk of contamination of toxic subtances; and the eutrophication can occur. Therefore, coastal water quality was monitored at Tra Co, Cua Luc and Do Son in 2015. The results showed that sea water had the higher concentration of nitrate and 4.4’DDD compared to limit values. RQ coefficient of coastal areas was medium (0.25 < 0.562 < 0.75), hence “environmental safety”. According to the SWQI index, the water quality in three stations was good and not polluted. In terms of eutrophication level classification according to OECD (1982), the water body of all stations was mesotrophic. According to classification by TRIX index, only water body of Do Son station was in a state of eutrophication, that of the remaining stations was mesotrophic.